ANALISIS PENGARUH DPK, NPF, ROA, PENEMPATAN DANA PADA SBIS, DAN TINGKAT BAGI HASIL TERHADAP PEMBIAYAAN BAGI HASIL (Studi Pada Bank Umum Syariah di Indonesia Periode Tahun 2010-2014) - Gumilarty, Gittrys Ratu Mashita; Indriani, Astiwi (Diponegoro Journal of Management, 2016)
This  research  aimed  to  analyze  the  influence  of  Third  Party  Fund  (DPK),  Non  Performing Financing (NPF), Return On Assets (ROA), placements of funds in SBIS, and equivalent rate of profit sharing toward profit and loss sharing financing. Case study on Islamic Banks in Indonesia Bank in period 2010-2014.Research population used was Islamic Banks in Indonesia Bank in period 2010-2014. Sampling tehnique used was purposive sampling and obtained a sample of 5 Islamic Banks by removing outliers from 2 samples of data banks, so that data is processed only numbered 60 data. The data used in this research were obtained from the Quarterly Report 2010-2014. Analysis technique used was multiple regression that includes classic assumption test, F statistic test, t statistic test, and coefficient of determination test (R2)The  result  of  this  research  showed  that  Third  Party  Fund  (DPK),  Non  Performing Financing (NPF), and Return On Assets (ROA) had positive significant affect to profit and loss sharing financing. Placements of funds in SBIS had positive not significant affect to profit and loss sharing financing. Equivalent rate of profit sharing had negative not significant affect to profit and loss sharing financing. The result of coefficient of determination test (R2) showed the ability of model prediction was 98,2% while the remaining 1,8% influenced by other variables outside the research.